Application of lean practice in UUM parcel centre - Chow Kah Jun, Thomas; Iteng, Rosman (Universiti Utara Malaysia, 2020)
The application of lean thinking in service industry required high knowledge and experience of lean concepts to know what needs to be done and is complementary to strategic decision making (Maleyeff, Management Decision, 2006). However, the similarity of service industry and manufacturing are very small which can result in difficult to implement lean in specific organization. One of the difficulties is deciding which of the many lean tools to apply and when to apply them. Lean implementation is a transformational process and needs to support organizational development alongside process improvement (Jones D. a., 2000). This research presents a comprehensive lean approach, based on Value Stream Management, which make the possibilities to enhance the performance of a service, by determining and tackling its criticalities. The study is motivated by the growing need to extend lean concepts to the service industry and by a minimum availability of operating tools to support technical staff in this effort. To validate the approach, an application concerning UUM Parcel Centre submitting parcel process is presented. Result demonstrate the quality of the approach and confirm the significant improvements that can be obtained with the application of lean thinking in the service context (Liker, 2000). With the success of application of the VSM in UUM Parcel Centre process, three processes in the current state map had been combined into one single process using digital computing. This result in reducing 12 minutes in total lead time which is 8.7 percentage in the future state map. Hence, UUM Parcel Centre can be more advance and efficient with implementing elements of Industry 4.0 technologies.